The effect of zirconia and titanium surfaces on biofilm formation and on host-derived immunological parameters. Issue 10 (October 2021) - Kniha, K.; Heussen, N.; Modabber, A.; Hölzle, F.; Möhlhenrich, S.C.
Abstract: The aim of this study was to analyse the effect of zirconia and titanium surfaces on biofilm formation and host-derived parameters. Studies comparing zirconia and titanium surfaces were selected up to September 1, 2019. The outcome measures were surface roughness, contact angle, bacterial count, bacterial adherence, biofilm thickness, bacterial distribution, and specifically investigated biofilm and specific host-derived immunological parameters. Random-effects meta-analyses of in vitro and in vivo studies were conducted. A total of 39 studies were included for data extraction. In the systematic review data, 10 studies stated that zirconia accumulated less initial oral biofilm parameters, 16 investigations showed negligible inter-material differences, and only one study showed that zirconia attracted the most biofilm. However, in the meta-analysis, the bacterial coverage was found to be significantly superior for zirconia surfaces ( P  <  0.00001); the other outcome measures did not show any statistically significant differences between zirconia and titanium for the remaining parameters and the studies presented a substantial degree of heterogeneity. Overall, on the basis of the meta-analysis, the current data situation does not allow a clear preference for the use of zirconia or titanium.